Experimental study on the dynamic performance of an air-cooled proton exchange membrane fuel cell stack with ultra-thin metal bipolar plate. (15th October 2022) - Yu, Xianxian; Chang, Huawei; Luo, Xiaobing; Tu, Zhengkai
Abstract: In this paper, a compact 3 kW air-cooled fuel cell stack consists of 95 single cells with metallic bipolar plate is designed. Compared with graphite bipolar plates, metal stamping bipolar plates are lighter in weight, smaller in size and faster in heat conduction, therefore the transient behaviors of the voltage and temperature of each cell are analyzed. The results show that the heat distribution of the air-cooled fuel cell is very uniform, and the temperature difference between the inlet and outlet of cathode air of the fuel cell is lower than 15 °C. The individual cell voltage uniformity percentage variation value reaches 7% when the drop in the loading current is over 25 A. Moreover, the voltage uniformity variation value is higher than 4% when the loading current output exceeds 35A. Thus, a large drop in loading and a high loading current easily increase the voltage uniformity variation value. Long-term continuous operation has a negative influence on the performance of the stack, especially the last fuel cell near the anode outlet. Anode purging can effectively alleviate the uniformity percentage variation in the voltages. The designed air-cooled fuel cell exhibits good performance and strong environmental adaptability. Highlights: Ultra-thin gold-plated metal bipolar plates. The temperature difference in a single fuel cell is lower than 15 °C. Continuous operation has negative influence on the fuel cell near the anode outlet. The designed air-cooled stack exhibits strong environmental adaptability.